Modeling the Process of Financing Small Organizations - Morozko, Natalia; Morozko, Nina; Didenko, Valentina (Journal of Reviews on Global Economics, 2018)
Most small business organizations are constantly lacking financial resources. This situation is associated with a small amount of own funds and the difficulty of raising borrowed funds. In the prevailing conditions, the need for well-founded financing management, this ensures the stable financial condition of a small organization, increases. Modeling the process of financing an organization allows you to consider different financing options, to influence the most significant factors in a particular situation. It is proposed to use the cognitive approach for dynamic management of the financing process and the choice of a rational variant based on the logit model. Determination of the degree of influence of various factors is proposed to be determined using correlation-regression modeling. With the help of the proposed modeling of the financing process of a small organization, it is possible to forecast positive changes in financial performance.